2015
DOI: 10.1007/s10071-015-0908-7
|View full text |Cite
|
Sign up to set email alerts
|

Developmental stress impairs performance on an association task in male and female songbirds, but impairs auditory learning in females only

Abstract: In songbirds, early-life environments critically shape song development. Many studies have demonstrated that developmental stress impairs song learning and the development of song-control regions of the brain in males. However, song has evolved through signaller-receiver networks and the effect stress has on the ability to receive auditory signals is equally important, especially for females who use song as an indicator of mate quality. Female song preferences have been the metric used to evaluate how developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 66 publications
0
21
1
Order By: Relevance
“…Our finding of elevated ZENKir in dNCM of females from larger broods could indicate that developmental stress dampens the relatively higher response to novel acoustic stimuli. Our data cannot directly address this hypothesis because of our experimental design, but similar studies by Schmidt and colleagues (2013a) and Farrell and colleagues (2015;2016) support this conclusion.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Our finding of elevated ZENKir in dNCM of females from larger broods could indicate that developmental stress dampens the relatively higher response to novel acoustic stimuli. Our data cannot directly address this hypothesis because of our experimental design, but similar studies by Schmidt and colleagues (2013a) and Farrell and colleagues (2015;2016) support this conclusion.…”
Section: Discussioncontrasting
confidence: 53%
“…These results are consistent with the interpretation that females from different treatment groups memorized tutor song equally well and were equally good at referencing those memories. We cannot rule out the possibility that females from larger broods have a dampened perceptual sensitivity to song, as is suggested by other studies (Farrell et al, 2016), but the finding that females from large broods had lower overall response levels during operant trials suggests birds in this study had reduced motivation to respond to song. Given that our brood size manipulation had no impact on boldness per se, it is unlikely that such reduced response reflects a treatment effect on behavioral phenotype or "personality".…”
Section: Discussionmentioning
confidence: 51%
“…What this difference between the two tasks in this condition does highlight however, is i) that dogs, and probably other animals, are sensitive to rather subtle methodological changes in prosociality studies and ii) the social facilitation control is an extremely important condition to include in order to disentangle any differences between test and non-social control conditions (see also [2]). Other than the current study and the previous bar-pull task, this control has only been used in one other PCT paradigm study to date and the authors also found that chimpanzees chose the prosocial option equally often when the partner was, and was not, able to access the food [8].…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly employed experimental methodology for investigating these prosocial, or other-regarding, preferences is the prosocial choice test (PCT)- whereby individuals can typically choose between rewarding only themselves (selfish; 1/0) or rewarding themselves and their partners (prosocial; 1/1). These studies, however, have produced contradictory results, with findings seemingly being affected by the methodology, species and even specific individuals or dyads [2]. …”
Section: Introductionmentioning
confidence: 99%
“…[1]), and prosociality was subsequently considered a human hallmark. Prosociality, here defined as helping another individual at low or no cost to the self [1], has since been tested in a multitude of primates with sometimes positive, sometimes negative and sometimes mixed results per species (for a review, see [2]). One of the hypotheses that tries to explain the evolutionary reasons for this mixed pattern is the cooperative breeding hypothesis (CBH), originally developed based on the relatively high prosocial tendencies of cooperatively breeding common marmosets [3].…”
Section: Introductionmentioning
confidence: 99%